2003
DOI: 10.1542/peds.111.5.e590
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Intraventricular Hemorrhage in Very Low Birth Weight Premature Infants: A Retrospective Case-Control Study

Abstract: ABSTRACT. Objective. High-grade intraventricular hemorrhage (IVH) is an important cause of severe cognitive and motor neurologic impairment in very low birth weight infants and is associated with a high mortality rate. The risk of IVH is inversely related to gestational age and birth weight. Previous studies have proposed a number of risk factors for IVH; however, lack of adequate matching for gestational age and birth weight may have confounded the results. The purpose of this study was to identify variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
132
3
14

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(179 citation statements)
references
References 31 publications
17
132
3
14
Order By: Relevance
“…Increased serum levels of interleukin 6 were associated with severe IVH in extremely preterm infants. Regarding to infection, similar to what was described by other authors, in this study neonatal sepsis was associated with a larger number of IVH when compared to controls, but this association lacked statistical significance in the multivariate analysis [30][31][32].…”
Section: Discussionsupporting
confidence: 87%
“…Increased serum levels of interleukin 6 were associated with severe IVH in extremely preterm infants. Regarding to infection, similar to what was described by other authors, in this study neonatal sepsis was associated with a larger number of IVH when compared to controls, but this association lacked statistical significance in the multivariate analysis [30][31][32].…”
Section: Discussionsupporting
confidence: 87%
“…The first study failing to find a relationship included premature infants born from 1981 to 1984; 25 the subsequent two published studies involved premature infants born during the surfactant era. 26,27 In glaring contrast to previous studies, hypocapnia, not hypercapnia, was observed by Erickson et al 26 to be an important risk factor for severe IVH or periventricular leukomalacia in ventilated premature infants born from 1992 to 1994. In the third study, hypocapnia during the first day of life was actually found to be protective against IVH.…”
Section: Discussionmentioning
confidence: 79%
“…In the third study, hypocapnia during the first day of life was actually found to be protective against IVH. 27 Inconsistency in results between studies is likely due to the inclusion of infants of different gestational ages and birth weights, various proportions of outborn infants, different sample sizes, and changing goals for ventilation. Disparate criteria for IVH and different PaCO 2 cutoffs were often used, as well as many of the studies only used univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Inaccurate ETT placement may increase the infant's risk for pneumothorax and subsequent intraventricular hemorrhage. 12,13 Secondly, surfactant is often given prophylactically in the delivery room prior to radiographic confirmation of the ETT position. If the ETT is positioned too deep, right mainstem bronchus intubation may occur and surfactant may be preferentially given to the right lung.…”
Section: Discussionmentioning
confidence: 99%